Using "Ag in the Classroom" curricula: Teachers' awareness, attitudes and perceptions of agricultural literacy - Cynthia L. Malecki; Glenn D. Israel; Elena Toro (EDIS)
Florida's residents are more dependent than ever on agriculture, but for many the relationship is invisible. This is because it is masked by the proliferation of widely available food products on store shelves and numerous intermediaries in the food processing, distribution and marketing system. The mission of agricultural education today is to create an awareness of this progression as well as the need for the agricultural industry. Additionally, agricultural education should create awareness about how newly developed technologies have become an integral part of the world's production of food and fiber. This document is AEC 370, a publication of the Agricultural Education and Communication Department, Florida Cooperative Extension Service, Institute of Agricultural and Food Sciences, University of Florida. Publication date January, 2004.